2022
DOI: 10.3390/ijms23105586
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in PPT1 Knock-In Mice Are Associated with Inflammatory Activation of Microglia

Abstract: Infantile neuronal ceroid lipofuscinosis (INCL), the most severe form of neuronal ceroid lipofuscinoses, is caused by mutations in the lysosomal enzyme palmitoyl protein thioesterase 1 (PPT1). Typical symptoms of this disease include progressive psychomotor developmental retardation, visual failure, seizures, and premature death. Here, we investigated seizure activity and relevant pathological changes in PPT1 knock-in mice (PPT1 KI). The behavior studies in this study demonstrated that PPT1 KI mice had no sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Further, microglial activation is associated with seizure onset in a CLN1 mouse model [40]. Therefore, one potential interpretation is that NtBuHA treatment suppressed seizures via a reduction in neuroinflammation [40,42,44,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, microglial activation is associated with seizure onset in a CLN1 mouse model [40]. Therefore, one potential interpretation is that NtBuHA treatment suppressed seizures via a reduction in neuroinflammation [40,42,44,48].…”
Section: Discussionmentioning
confidence: 99%
“…2C). An additional indicator of neuroinflammation in CLN1 that intensifies with disease progression is microglial activation, detectable by the adoption of a pro-inflammatory morphology [39][40][41]. Morphological analysis of ionized calcium-binding adaptor molecule 1 (Iba1)-positive microglia in S1 and V1 revealed that Cln1 -/mice receiving NtBuHA exhibited an increased number of microglial process intersections and elongated average process length compared to untreated controls at both 2 and 6 months (Fig.…”
Section: Ntbuha Administration Reduces Afsm In Cln1 -/Primary Cortica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent study analysed the epileptic phenotype in mice transgenic for the lysosomal enzyme palmitoyl protein thioesterase 1 (PPT1). These mice develop epilepsy after 7 months of age, including increased microgliosis [ 99 ]. When treated with P2X7R antagonists, PPI transgenic mice experienced fewer seizures, further supporting the antiepileptogenic potential of P2X7R antagonism.…”
Section: The Role Of P2x7rs During Seizures and Epilepsymentioning
confidence: 99%
“…Further, GABA A R plays a central role in synchronising network neuronal activity, which are tightly associated with higher brain functions such as learning and memory(Nakazono et al, 2018). PPT1-KI mice carrying nonsense mutations in the CLN1/PPT1 gene exhibited reduced expression of GABA A R along with impaired gamma oscillation and seizure onset (Zhang et al, 2022). These findings indicate the importance of GABA A R in CLN1 disease.…”
Section: Introductionmentioning
confidence: 99%